2017
DOI: 10.2739/kurumemedj.ms6406
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Carcinoma Treated with Lenvatinib

Abstract: Anaplastic thyroid carcinoma (ATC), which accounts for 1%-2% of all malignant tumors of the thyroid, is known to be highly resistant to any therapy and has a 1-year survival rate of 5%-20% [1][2][3]. ATC patients are limited in number, and most die within 6 months after diagnosis, making it difficult to establish a standard treatment protocol. Multimodal therapy including surgery, radiotherapy and chemotherapy has been introduced, but survival times remain poor [4][5][6].The use of molecular-targeted drugs as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Taking DTC for reference, common targeted drugs can be divided into BRAFdirected inhibitors, multikinase inhibitors, and mTOR inhibitors (21). Ohkubo et al (22) described the case of an ATC patient with lung metastasis, whose pulmonary nodules became hollow after lenvatinib (a multikinase inhibitor) administration. Subbiah et al (23) used dabrafenib and trametinib (BRAF-directed inhibitors) for locally advanced or metastatic BRAF V600E-mutant ATC patients, receiving an overall response rate of 69% and oneyear survival of 80%, which can also be a reminder of trying combined targeted drugs and routine genetic mutations tests in ATC patients for better medical guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Taking DTC for reference, common targeted drugs can be divided into BRAFdirected inhibitors, multikinase inhibitors, and mTOR inhibitors (21). Ohkubo et al (22) described the case of an ATC patient with lung metastasis, whose pulmonary nodules became hollow after lenvatinib (a multikinase inhibitor) administration. Subbiah et al (23) used dabrafenib and trametinib (BRAF-directed inhibitors) for locally advanced or metastatic BRAF V600E-mutant ATC patients, receiving an overall response rate of 69% and oneyear survival of 80%, which can also be a reminder of trying combined targeted drugs and routine genetic mutations tests in ATC patients for better medical guidance.…”
Section: Discussionmentioning
confidence: 99%
“…ATC is one of the most lethal carcinomas and is generally refractory to standard therapies ( 9 ). The knowledge of the genomic landscape of ATC has become extremely important since it allows the use of new drugs targeting specific molecular alterations ( 1 ). Among the actionable mutations that occur in ATC, the most common is BRAF p.V600E (50–70%) ( 4 ) Combined therapy with the BRAF inhibitor dabrafenib and the MEK inhibitor trametinib was approved by the FDA in 2018 for ATC harboring BRAF p.V600E mutations, either in stage IVC or in IVB ( 2 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anaplastic thyroid carcinoma (ATC) accounts for 1–2% of all thyroid malignancies. Despite its rarity, ATC is one of the most aggressive solid tumors in humans, with a median survival of 5–6 months ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A very recent Japanese study confirmed lenvatinib superiority compared to a palliative treatments approach, albeit with a median OS of only 4.2 months (Iwasaki et al 2020). Moreover, occasional casereports showed some efficacy (Oishi et al 2017, Ohkubo et al 2018, Kanazawa & Kammori 2019. Besides the Japanese experience, results on American patients are less encouraging, consistent with the results of our study: a small case-series on three ATC patients showed only transitory effects, with high toxicity rate (Iñiguez-Ariza et al 2017), and another study on ten patients showed a morphological control (SD+PR) in 70%, but with a PFS of only 2.7 months (Iyer et al 2018).…”
Section: :1mentioning
confidence: 99%
“…Initial results in a phase II study on 17 Japanese ATC patients were promising with an objective response rate of 24%, a disease control rate of 94%, a median PFS of 7.4 months (95% CI: 1.7-12.9) and a median OS of 10.6 months (Tahara et al 2017, Takahashi et al 2019. Case reports of off-label treatment have also been reported with controversial results in terms of efficacy (Iñiguez-Ariza et al 2017, Oishi et al 2017, Iyer et al 2018, Koyama et al 2018, Ohkubo et al 2018, Kanazawa & Kammori 2019. One of the drawbacks of the use of anti-vascular endothelial growth factor (VEGF) drugs in ATC is the risk of fatal bleeding in case of tumor invasion of the upper aerodigestive tract or predisposing conditions, such as previous high-doses external beam radiotherapy (Lamartina et al 2016), which are frequent situations in ATC; this risk might be limited with the use of initial reduced daily doses (Locati et al 2019).…”
Section: Introductionmentioning
confidence: 99%